Analisis Nilai Perjuangan Tokoh Dalam Novel Melangkah Karya J.S. Khairen Dan Implikasinya Terhadap Pembelajaran Sastra Di SMA - Gemitaria Gemitaria; Patrisia Cuesdeyeni; Yuliati Eka Asi; Alifiah Nurachmana; Hengki Rison; Dan Jaya Kusuma (Universitas Palan, 2023)
This research aims to: (1) Describe the value of the character's self-sacrificing struggle in the novel Step by J.S. Khairen. (2) Describe the value of the struggle for unity of the characters in the novel Step by J.S. Khairen. (3) Describe the value of the struggle for respect for the characters in the novel Step by J.S. Khairen. (4) Describe the value of the character's patient struggle in the novel Step by J.S. Khairen. (5) Describe the value of never giving up struggle of the characters in the novel Step by J.S. Khairen. (6) Describe the value of the character's cooperative struggle in the novel Step by J.S. Khairen. (7) Describe the implications regarding the value of the character's struggle in the novel Step by J.S. Khairen on literature learning in high school. This research is descriptive research with a qualitative research approach. The data collection techniques used are library techniques, listening techniques and further note-taking techniques. The data analysis technique uses text analysis techniques.The results of this research show that there are values of the characters' struggle in the novel Step by J.S. Khairen which is in accordance with Joyomartono's theory. The author found 25 data which were divided into six, namely 9 data on the value of being willing to sacrifice, 5 data on the value of unity, 2 data on the value of respect, 2 data on the value of patience, 4 data on the value of never giving up, 3 data on the value of cooperation. Apart from that, these values can be implied by studying literature in high school. Based on the 2013 curriculum in KD 3.8 interpret the author’s view of life in the novel read. and KD 4.8 Present the results of the interprestation of the author’s views both orally and in writting. The results of this study can be used as teaching material in studying literature in high school. Teaching materials can be used as a complement to the main textbook source.